2014
DOI: 10.1108/ijpsm-06-2011-0079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of public policy advocacy: challenges, principles and BEST-AC case study

Abstract: Purpose – The purpose of this paper is to demonstrate that both the processes and outcomes of advocacy can be evaluated in ways that can help with learning and accountability. The paper reviews the literature on evaluating advocacy, with a particular focus on development work, and describes an example of the systematic evaluation of the Business Environment Strengthening in Tanzania-Advocacy Component business advocacy programme in Tanzania. Design/meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Th e low level of use of evaluation by NGOs-only about one quarter of US advocacy organizations have reported that they engage in it ( Innovation Network, 2008 )-is not surprising given that many organizations do not have written advocacy plans to begin with ( Coates & David, 2002 ;Mansfi eld, 2010 ), let alone systematic assessments of this aspect of their work ( Almog-Bar & Schmid, 2014 ;Innovation Network, 2008 ). One reason for the low prevalence of advocacy evaluation is that NGOs have limited human and fi nancial resources to devote to it ( Bagnell Stuart, 2007 ;Coff man, 2009 ;Fine, 2007 ;Jones, 2011 ). A second reason is that advocacy evaluation can be nebulous and poses multiple challenges, which are summarized later in this article.…”
Section: State Of the Field: Emerging Practicementioning
confidence: 99%
See 4 more Smart Citations
“…Th e low level of use of evaluation by NGOs-only about one quarter of US advocacy organizations have reported that they engage in it ( Innovation Network, 2008 )-is not surprising given that many organizations do not have written advocacy plans to begin with ( Coates & David, 2002 ;Mansfi eld, 2010 ), let alone systematic assessments of this aspect of their work ( Almog-Bar & Schmid, 2014 ;Innovation Network, 2008 ). One reason for the low prevalence of advocacy evaluation is that NGOs have limited human and fi nancial resources to devote to it ( Bagnell Stuart, 2007 ;Coff man, 2009 ;Fine, 2007 ;Jones, 2011 ). A second reason is that advocacy evaluation can be nebulous and poses multiple challenges, which are summarized later in this article.…”
Section: State Of the Field: Emerging Practicementioning
confidence: 99%
“…Th e literature concurs that the foremost reason for NGOs to undertake assessment of their advocacy work is to gain knowledge to improve strategy ( Almog- Bar & Schmid, 2014 ;Bagnell Stuart, 2007 ;Beer & Reed, 2009 ;Borgman-Arboleda & Clark, 2009 ;Coe & Schlangen, 2011 ;Coff man, 2009 ;Forti, 2012 ;Fyall & McGuire, 2015 ;Guthrie, Louie, & Foster, 2005 ;Innovation Network, 2009 ;Jackson, 2014 ;Mulholland, 2010 ). NGOs engaging in advocacy indicate that the greatest benefi t of evaluation is that it assists them in refi ning strategies and determining the next steps in a campaign ( Innovation Network, 2008 ).…”
Section: Opportunities and Challenges In Evaluating Advocacymentioning
confidence: 99%
See 3 more Smart Citations